Two women performers - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two woman performers posing together. The woman on the left is sitting on a stool and holding a guitar. The woman on the right is holding a microphone with her left hand and has her right hand on the first woman's shoulder.